Penerapan model pembelajaran Problem Based Learning terhadap hasil belajar dan minat siswa pada materi laju reaksi di SMA Katolik Medan XI IPA 4 - Purba, Ernita; Munzirwan, Rudi (ARKA INSTITUTE, 2022)
This study aims to determine the improvement of learning outcomes of Trisakti Catholic High School students by applying the PBL learning model to the reaction rate material and to determine the response of Trisakti Catholic High School students by applying the PBL learning model to the reaction rate topic. This type of research is experimental research. The population in the study were students of class XI IPA Trisakti Catholic High School. The sample of this study was all students of XI IPA-4 Trisakti Catholic High School as many as 30 students. Sampling was carried out using the purposive sampling method. The analysis techniques used were the average test score, percentage of increase in learning outcomes, normality test, homogeneity test, hypothesis test and gain test. The results showed that the data were normally distributed and homogeneous and the average value of the experimental class posttest data was greater than the pretest. The PBL learning model developed on the reaction rate topic was higher than the KKM value set. It can be concluded that the chemistry learning outcomes of students who were taught with the PBL learning model developed on the reaction rate topic increased student learning outcomes.